Precision nutrition guided by genomic and functional assessments in postmenopause: a case report - Noland, Jenny (Frontiers in Nutrition, 2026)
Postmenopause is commonly associated with vasomotor symptoms, musculoskeletal discomfort, weight gain, gastrointestinal (GI) disturbances, and increased cardiometabolic and autoimmune risk. A 52-year-old woman presented with hot flashes, weight gain, joint stiffness and pain, and abdominal bloating. Genomic profiling revealed variants affecting methylation, detoxification, and metabolic regulation. Functional testing identified global sex hormone decline, impaired Phase II estrogen metabolism, vitamin D insufficiency, an atherogenic lipid profile, increased intestinal permeability, and elevated toxin burden. A phased, precision nutrition plan was implemented, combining dietary modification, targeted nutraceuticals, gut-directed therapy, detoxification support, sleep optimization, and stress management, alongside bioidentical hormone replacement therapy (BHRT). After 6 months, the patient experienced resolution of vasomotor symptoms and GI bloating, marked reduction in musculoskeletal pain and Medical Symptoms Questionnaire (MSQ) scores, improved sleep quality, and favorable lipid changes. This case demonstrates the potential of genomically informed precision nutrition, integrated with functional testing, to guide personalized interventions that enhance metabolic health, symptom resolution, and overall quality of life (QoL) in postmenopausal women.